The impact of an educational game on rational drug use and society’s attitudes towards the role of nurses - Dolu, İlknur; Önal, Yakup; Taşkaya, Zehra; Savci, Sema Nur; Yilmaz, Fatih (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Despite critical role of nurses in managing medication1, public perspectives of the role nurses play in rational drug use is still unclear. The study aimed to asess the impact of the “HEALTHgain” game, an educational tool, on enhancing individual comprehension of proper medication usage and their perceptions of the significance of the contributions of nurses in society. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This pretest-post-test, randomized control study took place betweenn May and November 2022 in Turkey. Two-hundred and thirty seven individuals aged 18 years and above were recruited. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The “HEALTHgain” game had a noteworthy impact on the knowledge of rational drug usage (F(1)=45.739, p<0.001) and attitudes of society towards a nurse’s role in rational drug use between the baseline and end measurements after 14-day of playing the game (F(1)=283.434, p<0.001). Morover, there were a significant improvement in both intervention and control group knowledge level of rational drug use between the initial and final assessments after a two-week period of game play, though it had not been presented in any table (t=-3.824, p<0.001 for control group; t=-35.492, p<0.001 for intervention group). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The study recommends that enhancing the game through contributions from various disciplines could elevate the rational use of medical knowledge and positively influence individual attitudes toward the role of nurses.